Direct observation of methoxycarbonylnitrene. Issue 35 (13th April 2017) - Li, Hongmin; Wu, Zhuang; Li, Dingqing; Wan, Huabin; Xu, Jian; Abe, Manabu; Zeng, Xiaoqing
Abstract : Methoxycarbonylnitrene CH3 OC(O)N, the missing link in the frequently studied Curtius-rearrangement of CH3 OC(O)N has been directly observed by using matrix-isolation IR and EPR spectroscopy. Abstract : The simplest alkoxycarbonylnitrene, CH3 OC(O)N, has been generated through laser (266 and 193 nm) photolysis of CH3 OC(O)N3 and CH3 OC(O)NCO and subsequently characterized by IR ( 15 N, D-labelling) and EPR (| D / hc | = 1.66 cm −1 and | E / hc | = 0.020 cm −1 ) spectroscopy in cryogenic matrices. Two conformers of the nitrene, with the CH3 group being in syn or anti configuration to the CO bond, have been unambiguously identified. Further UV light irradiation (365 nm) of the nitrene results in isomerization to CH3 ONCO, completing the frequently explored mechanism for the Curtius-rearrangement of CH3 OC(O)N3 .